(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article aims to explore how cartoon as a pedagogical material can be employed in language classroom from a constructivist point of view. It presents the characteristics of cartoon that bring much valuable impacts to language learning. The article discusses both the efficiency of animated cartoon as a genuine audiovisual learning material and how it can be employed in language classroom in order to satisfy the intended pedagogical outcomes of the 21st century.